Hubungan antara Pemenuhan Kebutuhan Psikologis dengan Perilaku Agresi pada Anak Jalanan - Sandy Nurhuda; Nur Aziz Affandi; Tatik Imadatus Sa’adati; Imron Muzakki (Gunung Djati Conference Series, 2023)
Nowadays, street children are found everywhere, especially in public places. These street children often perform behavior that disturbs the community. One of the behaviors that is often carried out is aggressive behavior, both physical and verbal aggression. The purpose of this study was to determine aggressive behavior on street children in Bandung. The method used is descriptive method with the characteristics of the respondents, namely male street children aged 13-18 years and included in the classification of "Children of the street" and "Children on the street". Data collection was carried out using a measuring instrument for aggressive behavior based on Buss' theory of aggression. The result is that street children show a high frequency of aggressive behavior, both physical aggression and verbal aggression.